Determination of Temperature Dependent Growth Parameters in Psychrotrophic Pathogen Bacteria and Tentative Use of Mean Kinetic Temperature for the Microbiological Control of Food - De Silvestri, Andrea; Ferrari, Enrico; Gozzi, Simone; Marchi, Francesca; Foschino, Roberto (Frontiers in Microbiology, 2018)
Temperature is the main factor to control the microbial growth in perishable foods. The psychrotrophic pathogen bacteria are microorganisms of concern for food products with extended shelf life in chilling conditions. The aims of this work were two. Firstly, to evaluate growth behaviour of Aeromonas hydrophila DSM-30187, Listeria monocytogenes DSM-20600 and Yersinia enterocolitica DSM-27689 strains, at different temperatures (4, 7, 10, 15, 25, and 30°C) and starting cell concentrations (10 and 106 CFU/mL), in order to determine the activation energies (Ea) of the relevant lag phases and growth rates. Secondly, to investigate if Mean Kinetic Temperature (MKT) might be applied in recording temperature devices to alert a thermal abuse in a management control system for food safety. As expected, lag phase and growth rate proved to be heavily affected by temperature whereas the inoculum size did not. The Ea values involved in the duration of latent periods, calculated on the basis of the Arrhenius model, were comparable for A. hydrophila and L. monocytogenes strains (from 21.3 to 24.4 kcal/mol), while significantly differed for Y. enterocolitica (16.6 kcal/mol). The Ea values of growth rates were similar for A. hydrophila and L. monocytogenes strains (from 20.9 to 21.1 kcal/mol), while were considerably lower for Y. enterocolitica (from 14.2 to 16.7 kcal/mol). The use of MKT is widespread and well accepted in pharmaceutical field as convenient method for estimating drugs degradation in relation to storage temperature. The Ea value of the lag phase found for L. monocytogenes (23.9 ± 1.2 kcal/mol) was included in the MKT formula. In this work, the air temperature of two chilling rooms was monitored during the normal operating activity in a catering company for a period of eight months. The MKT profiles were then compared with those of mean temperatures in different conditions (short or prolonged events of thermal abuse) with the purpose to evaluate if it may be applicable to reduce false alarms without lowering the safety level of stored food.